2003
DOI: 10.1097/01.ta.0000031175.96507.48
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and Outcomes from Pediatric Traumatic Brain Injury

Abstract: Patients who died had significantly higher admission serum glucose values than those patients who survived (267 mg/dL vs. 135 mg/dL; p = 0.000). Admission serum glucose > or = 300 mg/dL was uniformly associated with death. Admission Glasgow Coma Scale score (odds ratio, 0.560; 95% confidence interval, 0.358-0.877) and serum glucose (odds ratio, 1.013; 95% confidence interval, 1.003-1.023) are independent predictors of mortality in children with traumatic head injuries. CONCLUSION Hyperglycemia and poor neurolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
9

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(114 citation statements)
references
References 12 publications
5
100
0
9
Order By: Relevance
“…Other studies in children with traumatic brain or head injury have also shown an association between poor neurological outcome and elevated admission blood glucose. 24,[26][27][28] Brain trauma patients with permanent neurological deficits and in a vegetative state were found to have significantly higher admission blood glucose concentrations than children with good neurological recovery or minimal deficits. In addition, the development of inpatient hyperglycemia in children with extensive burn injuries, covering more than 60% of total body surface area, was found to increase the risk of bacteremia and fungemia, reduce skin graft adhesion, and increase the mortality rate.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies in children with traumatic brain or head injury have also shown an association between poor neurological outcome and elevated admission blood glucose. 24,[26][27][28] Brain trauma patients with permanent neurological deficits and in a vegetative state were found to have significantly higher admission blood glucose concentrations than children with good neurological recovery or minimal deficits. In addition, the development of inpatient hyperglycemia in children with extensive burn injuries, covering more than 60% of total body surface area, was found to increase the risk of bacteremia and fungemia, reduce skin graft adhesion, and increase the mortality rate.…”
Section: Discussionmentioning
confidence: 96%
“…Large prospective randomized clinical trails are essential to compare the efficacy of different strategies [32,37,38,39,40]. These are not easy to perform in children with severe TBI since the number of children treated at each center is low.…”
Section: Discussionmentioning
confidence: 99%
“…1,29 Several studies have demonstrated the association of SH in critically ill children with mortality. [1][2][3][4][5][10][11][12][13][14][15][16] Specifically, peak and duration of SH appear to be associated with mortality. Peak BG concentrations tend to be much higher in nonsurvivors compared with survivors.…”
Section: Stress Hyperglycemia In Pediatric Critical Illnessmentioning
confidence: 99%
“…8,9 However, studies in children have challenged this assertion by observing that SH during critical illness is associated with poor outcomes. [1][2][3][4][5][6][7][10][11][12][13][14][15][16] Based on the premise that SH during critical illness is possibly harmful, tight glucose control (TGC) to normalize blood glucose (BG) concentrations has emerged as a rational but unproven therapy to improve outcomes in critically ill children. Studies of TGC in critically ill adults have had mixed results, with some observing worse outcomes from TGC.…”
Section: Introductionmentioning
confidence: 99%